Eksplorasi Peran Pendamping Sosial dalam Membangun Kepercayaan dan Partisipasi Keluarga Miskin pada Program Keluarga Harapan (PKH) di Kota Makassar - Mario Mario; Riri Amandaria; Musrayani Usman; Andi Nurlela; Andi Muhammad Arif Haris (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Poverty is a multidimensional problem that is not only related to economic aspects, but also social, cultural, and political, which affects the welfare of poor families. The Family Hope Program (PKH) in Makassar City is designed as a conditional social assistance program that aims to improve the welfare of poor families through the provision of financial assistance and increased access to basic services. This study aims to explore the role of social companions in building trust, factors that affect the participation of poor families, and obstacles in the implementation of PKH. The method used was descriptive qualitative with subjects of 10 beneficiary families and 3 social companions, data was collected through semi-structured interviews and participatory observations, then analyzed thematically using an inductive approach. The results of the study show that social companions play a crucial role as communication mediators who build trust through an empathetic and familial approach, which strengthens the sense of belonging to the program. Family participation is influenced by social capital, local cultural norms, education levels, as well as bureaucratic constraints and access to services. Barriers such as social stigma, complicated bureaucracy, and limited companion training hinder the effectiveness of the program. Habermas's theory of communicative action and Durkheim's social solidarity support the finding that open dialogue and harmonious relationships between companions and families are key to successful social empowerment. It was concluded that strengthening the capacity of companions, simplifying bureaucracy, and increasing participatory dialogue spaces are needed to increase the effectiveness and sustainability of PKH in Makassar.